Regulating "Nirvana": Sustainable surf tourism in a climate of increasing regulation. Issue 1 (February 2015) - Ponting, Jess; O'Brien, Danny
Highlights A response to the issue of crowding in a sport tourism context is analysed. Physical carrying capacity regulation alone is inadequate to address crowding issues. Current regulatory regimes fail to address behavioural management and social carrying capacity. Vocational training and cultural interchange positioned as social adjuncts to purely physical capacity regulation. Links between recreational carrying capacity and sustainability are highlighted.